An antiviral principle present in a purified fraction from Melia azedarach L. leaf aqueous extract restrains Herpes simplex virus type 1 propagation - Alché, Laura E. (2002)
Meliacine (MA), an antiviral principle isolated from leaves of Melia azedarach L., exhibits potent antiviral activity against herpes simplex virus type 1 (HSV-1) by inhibiting specific infected-cell polypeptides (ICPs) produced late in infection. Some of these are involved in DNA synthesis and in the assembly of nucleocapsids. The present report provides additional evidence to elucidate the mode of action of MA against HSV-1. Time-of-addition experiments confirmed that MA affects a late event in the multiplication cycle of HSV-1. We showed that MA diminished the synthesis of viral DNA and inhibited the spread of infectious viral particles when HSV-1 that expresses -galactosidase activity was used. In addition, the lack of a protein with an apparent MW of 55 KD was detected in MA-treated cell extracts. Ultrastructural analysis of infected cells showed that, in the case of MA treatment, a large number of unenveloped nucleocapsids accumulated in the cytoplasm and a minor proportion of mature virus was found in cytoplasmic vesicles. These findings suggest that MA exerts an antiviral action on both the synthesis of viral DNA and the maturation and egress of HSV-1 during the infection of Vero cells.